2005
DOI: 10.1111/j.1442-2042.2005.01010.x
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor‐C (VEGF‐C) expression predicts lymph node metastasis of transitional cell carcinoma of the bladder

Abstract: Purpose : It has been found that expression of vascular endothelial growth factor-C (VEGF-C) in several carcinomas is significantly associated with angiogenesis, lymphangiogenesis and regional lymph node metastasis. However, VEGF-C expression in bladder transitional cell carcinoma (TCC) has not yet been reported. To elucidate the role of VEGF-C in bladder TCC, we examined VEGF-C expression in bladder TCC and pelvic lymph node metastasis specimens obtained from patients who underwent radical cystectomy. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
3
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 32 publications
1
43
3
2
Order By: Relevance
“…Among 1,384 genes that were regulated by BLACAT2 (P < 0.05, fold changes > 2.0), multiple genes that play critical roles in lymphatic metastasis, such as VEGF-C, SNAI2, and MMP9 (33)(34)(35), were significantly downregulated in BLACAT2-silenced cells ( Figure 5A). Furthermore, immunostaining and qPCR analyses revealed that the expression of VEGF-C, SNAI2, and MMP9, at both the mRNA and the protein levels, was increased in BLACAT2-transduced cells and decreased in BLACAT2-silenced cells ( Figure 5, B-D, and Supplemental Figure 13, A-E).…”
Section: Blacat2 Regulates Vegf-c Snai2 and Mmp9 Expressionmentioning
confidence: 99%
“…Among 1,384 genes that were regulated by BLACAT2 (P < 0.05, fold changes > 2.0), multiple genes that play critical roles in lymphatic metastasis, such as VEGF-C, SNAI2, and MMP9 (33)(34)(35), were significantly downregulated in BLACAT2-silenced cells ( Figure 5A). Furthermore, immunostaining and qPCR analyses revealed that the expression of VEGF-C, SNAI2, and MMP9, at both the mRNA and the protein levels, was increased in BLACAT2-transduced cells and decreased in BLACAT2-silenced cells ( Figure 5, B-D, and Supplemental Figure 13, A-E).…”
Section: Blacat2 Regulates Vegf-c Snai2 and Mmp9 Expressionmentioning
confidence: 99%
“…Therefore, expression and the processing status of VEGF-C and D in a given tissue appear to determine the lymphangiogenic and angiogenic activities of these growth factors [171]. Expression of VEGF-C in tumor tissue serves as a reliable marker for ongoing tumor lymphangiogenesis and increased risk of regional lymph node metastasis in many cancer types [172,173]. Data for VEGF-D are less consistent suggesting that its ability to promote metastatic spread via lymphatics depends on the investigated cancer type and/ or grade [174][175][176].…”
Section: Tumor-induced Lymphangiogenesismentioning
confidence: 99%
“…Vascular endothelial growth factor-C (VEGF-C) has been associated with angiogenesis, lymphangiogenesis and regional lymph node metastasis and was reported to have an anti-apoptotic and proliferative role (23). It was reported that the involvement of VEGF-C expression in the promotion of lymph node metastasis could be used as a decision-making biomarker for selected patients with invasive bladder cancer who underwent bladder-preserving radical surgery and were associated with an anti-apoptotic phenotype (24)(25)(26). RNA interference-mediated VEGF-C reduction suppresses malignant progression and enhances mitomycin C sensitivity of bladder cancer T24 cells (27).…”
Section: Introductionmentioning
confidence: 99%